2014
DOI: 10.1016/j.cmet.2014.03.025
|View full text |Cite
|
Sign up to set email alerts
|

A Smooth Muscle-Like Origin for Beige Adipocytes

Abstract: SUMMARY Thermogenic UCP1-positive cells, which include brown and beige adipocytes, transform chemical energy into heat and increase whole body energy expenditure. Using a selective translational profiling approach, we present a comprehensive molecular description of brown and beige gene expression in vivo. This UCP1-TRAP dataset demonstrates striking similarities and important differences between these cell types, including a smooth muscle-like signature expressed by beige, but not classical brown adipocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
365
4
9

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(393 citation statements)
references
References 50 publications
15
365
4
9
Order By: Relevance
“…16 A recent paper reported that~10% of the UCP1-positive beige adipocytes in inguinal WAT arise from smooth muscle precursors that express Myh11. 17 In addition, a subset of beige adipocytes in anterior subcutaneous and perigonadal WAT depots originates from Myf5-positive cells, 18 whereas most of beige adipocytes in inguinal WAT derive from Myf5-negative precursors. These data suggest high cellular heterogeneity of beige adipocyte populations in multiple WAT depots.…”
Section: Developmental Lineages Of Brown and Beige Adipocytes In Micementioning
confidence: 99%
“…16 A recent paper reported that~10% of the UCP1-positive beige adipocytes in inguinal WAT arise from smooth muscle precursors that express Myh11. 17 In addition, a subset of beige adipocytes in anterior subcutaneous and perigonadal WAT depots originates from Myf5-positive cells, 18 whereas most of beige adipocytes in inguinal WAT derive from Myf5-negative precursors. These data suggest high cellular heterogeneity of beige adipocyte populations in multiple WAT depots.…”
Section: Developmental Lineages Of Brown and Beige Adipocytes In Micementioning
confidence: 99%
“…These adipocytes are commonly referred to as beige, brite (from brown in white), inducible, or recruitable, reviewed in Chechi et al 7 and seem to result from the transdifferentiation of previously unilocular, white adipocytes4, 5 and from the de novo differentiation of precursor cells 8. It has been proposed that beige adipocytes can derive from a distinct precursor and display a gene expression pattern different from that of brown adipocytes 9. Recent studies also reported the presence of BAT and the formation of UCP1‐expressing adipocytes within WAT depots in adult humans 10, 11.…”
Section: Introductionmentioning
confidence: 99%
“…8 Over the past several years, the field of brown and beige fat biology has seen an increase in the number of reports implicating various growth factors and cytoskeleton dynamics in the regulation of brown and beige fat development. More recently, we and others have demonstrated that beige adipocytes arise from a smooth-muscle origin, 10,12 suggesting that morphogenetic signals may regulate a cell fate switch between smooth muscle cells and beige adipocytes. In this review, we will focus on the effects of morphogens on cell shape and cytoskeleton dynamics.…”
Section: Introductionmentioning
confidence: 87%